PELATIHAN TENTANG PENGENDALIAN KAS PERUSAHAAN PADA SISWA-SISWI SMA HARAPAN JAYA - Hastuti, Rini Tri; Prajogi, Muhammad Bintang; Kho, Christian (Jurnal Serina Abdimas, 2023)
The purpose of this training is to help Harapan Jaya high School students understand in depth the science of Accounting which is related to the company's cash control. Accounting subject matter at the high school level is only limited to basic accounting material and focuses more on the preparation and reporting of financial statements. The results of interviews with schools, especially teachers of accounting subjects, we were asked to provide material by taking the scope of the company's internal control. This internal control material has not yet been included in the accounting curriculum, so the teacher asked us to provide the material. Internal control covers all the scope of each transaction and forecast in the financial statements. In this training we take the scope of internal control for cash forecasting. The data used in this training is primary data obtained directly from Harapan Jaya high School such as data from interviews with principals and teachers. As for secondary data obtained from books, journals, internet that support this training. The output of the results of this Community Service is the proceedings of the national seminar as a presenter and also the articles are uploaded to PINTAR as additional outputs. ABSTRAK Tujuan pelatihan ini adalah untuk membantu siswa-siwi SMA Harapan Jaya memahami ilmu Akuntansi secara mendalam yang dikaitkanpengendalian kas perusahaan. Materi pelajaran akuntansi di tingkat SMU hanya terbatas pada materi akuntansi yang bersifat dasar dan lebih berfokus pada penyusunan dan pelaporan laporan keuangan. Hasil interview dengan pihak sekolah khususnya guru mata pelajaran akuntansi, kami diminta untuk memberikan materi dengan mengambil ruang lingkup pengendalian internal perusahaan. Materi pengendalian internal ini belom masuk dalam kurikulum pelajaran akuntansi, sehingga pihak guru meminta kami memberikan materi tersebut. Pengendalian internal meliputi semua ruang lingkup dalam setiap transaksi dan perkiraan dalam laporan keuangan. Dalam pelatihan ini kami mengambil ruang lingkup pengendalian internal untuk perkiraan kas. Data yang digunakan dalam pelatihan ini yaitu data primer yang diperoleh langsung dari pihak SMA Harapan Jaya seperti data hasil wawancara dengan kepala sekolah dan guru. Sedangkan untuk data sekunder diperoleh dari buku, jurnal, internet yang mendukung pelatihan ini. Luaran dari hasil Pengabdian Kepada Masyarakat ini adalah proceeding seminar nasional sebagai pemakalah dan juga aritkel di muat di PINTAR selaku luaran tambahan.